Sensory Characteristics and Nutritional Values of Taiyaki with the Addition of Spirulina sp. - Nurinsani, Anisa Eka
Spirulina is known as a superfood because it is a food source rich in both macro and micro nutrients. According to Jung et al. (2019) Spirulina has high levels of protein, various essential amino acids, high levels of polyunsaturated fatty acids (PUFAs), phycocyanins, almost all essential vitamins, high levels of potassium, antioxidants, and many other vitamins and minerals. Taiyaki is known to the Indonesian people as a snack originating from Japan, taiyaki is also popular as a typical Korean snack with the name bungeo-ppang. Based on this, it is expected that the addition of Spirulina sp. powder can add to the nutritional value of taiyaki, especially the protein component so that food/snack choices will be created that are not only attractive but also have better nutritional value. The research design consisted of four treatments and five replications. Spirulina sp. powder added to the weight of the taiyaki filling, namely: 0%, 1%, 2%, and 3%. The results of the Kruskal Wallis test on the parameters of appearance, aroma, and texture showed that P>0.05 so that there was no significant difference in the treatments (P0, P1, P2, and P3), but the taste parameters showed that P<0.05 so there was a significant difference in the treatment (P0, P1, P2, and P3) of the taste of taiyaki with the addition of Spirulina sp. powder. Then the Mann-Whitney test was carried out on the taste parameter whose results showed that the preference level of the taste parameters was not significantly different (P>0.05) at P0 and P1, P1 and P2, P1 and P3, and P2 and P3, but there were significant different (P<0.05) at P0 and P2 as well as P0 and P3. The proximate test was carried out on control taiyaki and taiyaki with the best addition of Spirulina sp. powder (P1: 1% concentration), the determination of the best concentration is based on the highest average value of the hedonic test results. The control taiyaki showed the value of: 26.85% water, 2.75% ash, 2.71% protein, 2.57% fat, and 65.12% carbohydrates, while taiyaki with the addition of 1% Spirulina sp. indicated values: 26.55% water, 2.53% ash, 3.61% protein, 2.63% fat and 64.68% carbohydrates. These results indicate an increase in protein and fat levels.